2022
DOI: 10.33963/kp.a2022.0120
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-measured light-intensity physical activity and the risk of cardiovascular disease or death in older adults: A meta-analysis

Abstract: Background: Light-intensity physical activity (LPA) is related to a reduced risk of all-cause death in older adults, but its effect on cardiovascular disease or death remains questioned. This meta-analysis aimed to quantify the association of LPA with the risk of cardiovascular disease and death in older adults. Methods:We conducted a literature search in electronic databases for prospective cohort studies assessing the relationship between LPA measured by accelerometers and the risk of cardiovascular disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to the available evidence, it seems that the duration of physical activity has a quite important impact on the reduction of CVD risk [ 151 ] but the intensity of exercise should be adapted to the cardiorespiratory capacity and medical conditions of the individual [ 134 ]. A meta-analysis of 5 cohort studies that measured the intensity of physical activity by an accelerometer in older adults found that HR for CVD risk was lower in moderate-to-vigorous physical activity than light-intensity physical activity although HR for CVD death was almost equal in light- and moderate-to-vigorous intensity physical activity [ 152 ], suggesting that moderate-to-vigorous intensity physical activity may be more beneficial for CVD incidence than light-intensity activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available evidence, it seems that the duration of physical activity has a quite important impact on the reduction of CVD risk [ 151 ] but the intensity of exercise should be adapted to the cardiorespiratory capacity and medical conditions of the individual [ 134 ]. A meta-analysis of 5 cohort studies that measured the intensity of physical activity by an accelerometer in older adults found that HR for CVD risk was lower in moderate-to-vigorous physical activity than light-intensity physical activity although HR for CVD death was almost equal in light- and moderate-to-vigorous intensity physical activity [ 152 ], suggesting that moderate-to-vigorous intensity physical activity may be more beneficial for CVD incidence than light-intensity activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behaviours have an adverse impact on health, regardless of physical activity, increasing mortality by all causes, including by cardiovascular diseases, the risk of cancer, the risk of metabolic disorders such as diabetes mellitus, hypertension and dyslipidaemia, the risk of musculoskeletal disorders such as arthralgia and osteoporosis, and the risk of depression and cognitive deterioration [ 2 , 3 , 4 ]. On the contrary, it has been shown that the more time spent doing physical activity, regardless of the type and intensity, the lower the morbidity and mortality due to cardiometabolic diseases, tumours and mental disorders, with an improvement in the quality of life and the benefits for the health system and society [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%